Tax malfeasance of high net-worth individuals in Malaysia: archival audited data and elite interviews / Rasyidah Che Rosli - Che Rosli, Rasyidah (Institute of Graduate Studies, UiTM, 2017)
The Luxembourg and Panama leaks reveal that tax malfeasance of high net-worth individuals (HNWIs) is a pervasive and universal problem. In Malaysia, financial scandal and domestic tax fraud cases have also surged significantly. However, published empirical research on tax malfeasance of HNWIs is scant. At the time of study, little is known about the determinants of tax malfeasance among HNWIs and how to improve tax compliance of HNWIs in Malaysia. This study aims to fill up a research void. The objectives of the study are (a) to analyse the profiles of Malaysian HNWIs who were caught to engage in tax malfeasance as a result of tax audits, (b) to examine if economic factors influence tax malfeasance among HNWIs, (c) to assess if non-compliance opportunity determinants influence tax malfeasance, (d) to investigate whether the involvement of tax professionals influence tax malfeasance among HNWIs, and (e) to examine if non-economic determinants play a role in tax malfeasance. This study has two stages. In Stage 1, archival data analysis method was employed. With written permission, the data of the 235 audited HNWIs that engaged in tax malfeasance from year 2009 to 2013 were obtained from the Inland Revenue Board of Malaysia (IRBM). Of the 235, 40 per cent of HNWIs were above 55 years old and a majority (89 per cent) were males and had multiple sources of income. A research model with five hypotheses was developed to examine the determinants of tax malfeasance among HNWIs.